2021
DOI: 10.1097/md.0000000000026939
|View full text |Cite
|
Sign up to set email alerts
|

Application of mentorship program for another aspect of surgical residency training

Abstract: Traditionally, surgical residency training is more focused on obtaining surgical skills through a well-established coaching system worldwide. However, constant advances in medical science require surgeons to learn not only surgical skills but also the ability of scientific research to improve clinical practice and future professional development. The study aims to emphasize that professional education in terms of scientific research is also significant for surgical residency training.All residents who had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The majority of programs are a dyad model where each mentee is assigned to one mentor. One general surgery residency mentorship program that required at least three mentor meetings annually and two social events showed that residents reported an improved perception of faculty involvement and support after the implementation of the program [41]. Another general surgery program described a "Mentor Match" design where both residents and attendings filled out surveys based on the six ACGME clinical competencies.…”
Section: Mentorship Programs Across Other Surgical Residency Programsmentioning
confidence: 99%
“…The majority of programs are a dyad model where each mentee is assigned to one mentor. One general surgery residency mentorship program that required at least three mentor meetings annually and two social events showed that residents reported an improved perception of faculty involvement and support after the implementation of the program [41]. Another general surgery program described a "Mentor Match" design where both residents and attendings filled out surveys based on the six ACGME clinical competencies.…”
Section: Mentorship Programs Across Other Surgical Residency Programsmentioning
confidence: 99%